Dampak citra dan karakteristik produk terhadap kepuasan pelanggan dan konsekuensinya terhadap loyalitas pelanggan - Muliansyah, Dadah; Nurhidayah, Rika; Ratnasari, Ani (Universitas Tangerang Raya, 2024)
The main challenges faced by MSMEs in Bandung include low purchasing power, increasingly tight competition, and risks related to customer loyalty. Based on this, this study aims to analyze the effect of product image and attributes on customer loyalty, both directly and indirectly through customer satisfaction. This study uses a quantitative approach in Bandung City, with the observation unit being Sambal Bakar Lengkong customers. The sample used consisted of 235 respondents taken using the Multistage Random Sampling technique. Causality analysis was carried out using Structural Equation Modeling. The results of the study indicate that: The image and product attributes of Culinary MSMEs in Bandung City contribute to forming customer satisfaction, but do not have a direct effect on customer loyalty; Customer satisfaction plays an important role in creating customer loyalty; Customer satisfaction functions as a mediator between the influence of image and product attributes on customer loyalty; Product attributes have a more significant influence than image in increasing customer satisfaction, which in turn will create customer loyalty. This study provides managerial insights to improve customer loyalty of Sambar Bakar Lengkong, with a focus on increasing customer satisfaction supported by the development of product attributes and image.